Inbreeding Alters the Chemical Phenotype and Mating Behavior of a Beetle - Müller, Thorben; Lachenicht, Laura; Müller, Caroline (Frontiers in Ecology and Evolution, 2018)
Mating between closely related individuals is often associated with fitness declines. However, less is known about consequences of inbreeding for (sexual) chemical signaling traits and for mate choice and acceptance. Thus, we investigated effects of inbreeding on the chemical phenotype, i.e., the profile and diversity of putative cuticular hydrocarbons (CHCs) in the leaf beetle Phaedon cochleariae Fabricius. Moreover, we tested mating probabilities in no choice bioassays with different combinations of outbred and inbred beetles. Finally, we tested male preferences and female aggression in a dual choice bioassay with one outbred male, one outbred and one inbred female. The chemical phenotype was altered in inbred females, which showed a male-like CHC profile. In no choice bioassays, inbred individuals had a decreased mating probability than outbred individuals. Changes in the chemical phenotype of inbred females might be involved in the negative inbreeding effects on mating acceptance. When having the choice, males did not show any preference between outbred and inbred females. However, inbred females were more aggressive in these situations, potentially to raise their chances to be mated, because due to inbreeding depression they have lower reproductive perspectives than outbred females. Overall, inbreeding effects on the chemical phenotype, mating acceptance and female aggression might have consequences for the population dynamics and development of the individuals. In conclusion, these results suggest that inbreeding events have the potential to affect sexual selection of chemical signaling traits and evolutionary processes underlying mating strategies.